Biotranslocation of lead and cadmium in Spinacia oleracea amended with Klebsiella sp. VITLLJ4: an effective microbe technology-based phyto-rhizoremediation study - Deo, Loknath; Osborne, Jabez William; Benjamin, Lincy Kirubhadharsini (Frontiers in Environmental Science, 2025)
Pollution caused by heavy metals (HMs) poses a significant threat to environmental and agricultural sustainability. The current study emphasizes on the isolation and characterization of lead (Pb)- and cadmium (Cd)-resistant bacteria from lake soil sediment. Among all the six isolates obtained, VITLLJ4 was capable of tolerating Cd and Pb up to concentrations of 600 ppm and 1,200 ppm, respectively. It also exhibited strong biofilm formation under metal stress with specific biofilm formation (SBF) values ranging at 0.32–1.06 for Pb and 0.38–0.91 for Cd, facilitating the sequestration of metals. Growth profiling of VITLLJ4 showed steady exponential growth under metal stress conditions, and response surface methodology (RSM) confirmed the optimization of pH, carbon source, and nitrogen source for efficient bioremoval of Cd and Pb. Scanning electron microscopy (SEM) revealed the presence of pleomorphism in cells upon exposure to HMs. Furthermore, VITLLJ4 exhibited plant growth-promoting rhizobacterial (PGPR) traits, revealing its ability to produce indole acetic acid, siderophore, and ammonia, and the isolate was also capable of solubilizing insoluble phosphate. A pilot-scale study on pot culture showed an increase in the phenotypic characteristics of Spinacia oleracea augmented with VITLLJ4 (rhizoremediation) than that in untreated plants (phytoremediation). The bioaccumulation of Pb and Cd was found to be higher in the roots than in the shoots of S. oleracea, confirming the plant to be a root accumulator for heavy metals. The maximum removal efficiency of Pb and Cd was found to be higher in rhizoremediation treatments, i.e. 80% and 75%, than in phytoremediation, i.e., 59% and 50%, upon supplementation of 150 ppm of Cd and Pb. These findings highlighted that microbe-assisted phytoremediation is an effective strategy in the bioremoval of Pb and Cd from polluted sites.